The Importance of Islamic Character Education in All Subjects - Maizatul, Maizatul; Oktavia, Gifa; Rahman, Ikhwan (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
Islamic guidance and counseling are closely related to Islamic Religious Education subjects because both aim to shape students with Islamic character. This Islamic character is formed based on the values contained in the Quran and Hadith as the main guidelines in life. This study aims to analyze the application of Islamic character education, not only limited to Islamic Religious Education subjects, but also integrated into other subjects. This shows that Islamic character building can be carried out comprehensively through a cross-curricular approach. The results of the analysis show that effective Islamic counseling services will be maximized if supported by learning from other subjects. Each subject has the potential to instill Islamic values that can strengthen the character of students. Thus, an integrative approach between Islamic counseling and all subjects is necessary in shaping a well-rounded Muslim personality. The findings in this study can be used as preliminary data and a reference for future researchers to examine this issue in a broader context and setting.